Life without Division: Physiology of Escherichia coli FtsZ-Deprived Filaments - Alicia Sánchez-Gorostiaga; Pilar Palacios; Rocío Martínez-Arteaga; Manuel Sánchez; Mercedes Casanova; Miguel Vicente (mBio, 2016)
ABSTRACT When deprived of FtsZ, Escherichia coli cells (VIP205) grown in liquid form long nonseptated filaments due to their inability to assemble an FtsZ ring and their failure to recruit subsequent divisome components. These filaments fail to produce colonies on solid medium, in which synthesis of FtsZ is induced, upon being diluted by a factor greater than 4. However, once the initial FtsZ levels are recovered in liquid culture, they resume division, and their plating efficiency returns to normal. The potential septation sites generated in the FtsZ-deprived filaments are not annihilated, and once sufficient FtsZ is accumulated, they all become active and divide to produce cells of normal length. FtsZ-deprived cells accumulate defects in their physiology, including an abnormally high number of unsegregated nucleoids that may result from the misplacement of FtsK. Their membrane integrity becomes compromised and the amount of membrane proteins, such as FtsK and ZipA, increases. FtsZ-deprived cells also show an altered expression pattern, namely, transcription of several genes responding to DNA damage increases, whereas transcription of some ribosomal or global transcriptional regulators decreases. We propose that the changes caused by the depletion of FtsZ, besides stopping division, weaken the cell, diminishing its resiliency to minor challenges, such as dilution stress. IMPORTANCE Our results suggest a role for FtsZ, in addition to its already known effect in the constriction of E. coli, in protecting the nondividing cells against minor stress. This protection can even be exerted when an inactive FtsZ is produced, but it is lost when the protein is altogether absent. These results have implications in fields like synthetic biology or antimicrobial discovery. The construction of synthetic divisomes in the test tube may need to preserve unsuspected roles, such as this newly found FtsZ property, to guarantee the stability of artificial containers. Whereas the effects on viability caused by inhibiting the activity of FtsZ may be partly overcome by filamentation, the absence of FtsZ is not tolerated by E. coli, an observation that may help in the design of effective antimicrobial compounds.